Active collision algorithm for autonomous electric vehicles at intersections. Issue 1 (10th October 2018) - Bian, Chentong; Yin, Guodong; Xu, Liwei; Zhang, Ning
Abstract : Various studies have been conducted on resisting network attacks on autonomous vehicles and vehicular networks. Invaded vehicles may cause severe damage and casualties; thus, it is essential to stop these vehicles to prevent traffic accidents and terrorist attacks. To improve traffic safety, an active collision algorithm based on trajectory planning is therefore proposed. The algorithm can be used to cause autonomous vehicles to collide with invaded vehicles at intersections. Several types of trajectory planning algorithms have been proposed for autonomous vehicles in recent years. However, a few of these algorithms consider active collisions with other vehicles. The main advantage and novelty of the proposed method are that it can be utilised to plan a suitable trajectory for active collision with invaded vehicles at intersections. This capability has rarely been discussed in the literature to date. The main contributions of this study are that the problem of active collision of autonomous vehicles at intersections is discussed and an effective active collision algorithm based on trajectory planning is proposed. The performance of the algorithm is demonstrated using simulation. The results show that the proposed algorithm is effective in enabling autonomous electric vehicles to collide with invaded vehicles at intersections.